Increased Heat Resilience of Intraspecific Outbred Compared to Inbred Lineages in the Kelp Laminaria digitata: Physiology and Transcriptomics - Liesner, Daniel; Pearson, Gareth A.; Bartsch, Inka; Rana, Shivani; Harms, Lars; Heinrich, Sandra; Bischof, Kai; Glöckner, Gernot; Valentin, Klaus (Frontiers in Marine Science, 2022)
Marine forests and kelps as their foundation species are threatened by ocean warming especially at the warm distributional edges. Previously identified genetic divergence and ecotypic differentiation within kelp species may allow to produce more resilient lineages by intraspecific outbreeding among populations. In a mechanistic investigation of heat stress, heterosis (hybrid vigour), and underlying gene expression patterns, we assessed the thermal performance of inbred (selfings) and outbred (reciprocal crosses) sporophytes of the N-Atlantic kelp Laminaria digitata among clonal isolates from two divergent populations; one from the temperate North Sea (Helgoland) and one from the Arctic (Spitsbergen). First, we investigated the upper thermal tolerance of microscopic sporophytes in a 14-day experiment applying sublethal to lethal 20–23°C. The upper survival temperature of microscopic sporophytes was lower for the inbred Arctic selfing (21°C) than for the temperate selfing and the reciprocal crosses (22°C). Only in the temperate selfing, 4.5% of sporophytes survived 23°C. We then subjected 4–7 cm long sporophytes to a control temperature (10°C), moderate (19°C) and sublethal to lethal heat stress (20.5°C) for 18 days to assess gene expression in addition to physiological parameters. Growth and optimum quantum yield decreased similarly in the reciprocal crosses and the temperate selfing at 19 and 20.5°C, while inbred Arctic sporophytes died within seven days at both 19 and 20.5°C. In response to 20.5°C, 252 genes were constitutively regulated across all surviving lineages, which we use to describe metabolic regulation patterns in response to heat stress in kelp. At sublethal 20.5°C, ca. 150 genes were differentially expressed by either crossed lineage in comparison to the temperate selfing, indicating that they maintained a growth response similar to the temperate selfing with differential metabolic regulation during sublethal heat stress. Subtle differences in physiology and the differential expression of nine genes between the reciprocal crosses at 20.5°C indicate that female and male gametophytes may contribute differently to offspring traits. We consider potential inbreeding depression in the Spitsbergen selfing and quantify the better performance of both crosses using heterosis-related parameters. We discuss the potential and risks of outbreeding to produce more resilient crops for mariculture and marine forest restoration.